2010
DOI: 10.1542/peds.2009-0052
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Neurodevelopment in Deformational Plagiocephaly

Abstract: OBJECTIVE We assessed the neurodevelopment of infants with and without deformational plagiocephaly (DP), at an average age of 6 months. METHODS The Bayley Scales of Infant Development III (BSID-III) were administered to 235 case subjects and 237 demographically similar, control participants. Three-dimensional head photographs were randomized and rated for severity of deformation by 2 craniofacial dysmorphologists who were blinded to case status. RESULTS We excluded 2 case subjects with no photographic evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 14 publications
9
79
0
4
Order By: Relevance
“…15,27,68 Other studies have proposed obstetric concerns such as constraints of the birth canal on firstborn babies, prolonged labor, breech position, assisted deliveries, intrauterine restrictions, and plural births. 39,54,63 The impact of supine sleeping position on PP is best illustrated by the AAP's 1992 recommendation for infants to sleep on their backs. 1 This BTS campaign decreased the incidence of SIDS by more than 40%, but increased consultations for PP by 600%.…”
Section: Established Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,27,68 Other studies have proposed obstetric concerns such as constraints of the birth canal on firstborn babies, prolonged labor, breech position, assisted deliveries, intrauterine restrictions, and plural births. 39,54,63 The impact of supine sleeping position on PP is best illustrated by the AAP's 1992 recommendation for infants to sleep on their backs. 1 This BTS campaign decreased the incidence of SIDS by more than 40%, but increased consultations for PP by 600%.…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…39,46 More recently, however, studies have built a possible association between disruptions in infant development and PP. 10,21,28,30,63 Multiple reports over the past decade have pointed to links between PP and abnormal ophthalmological findings, auditory processing, and motor development. 4,10,25,27,28,35,44,47,62,63,68 Two case-controlled studies, by Speltz et al 63 and Fowler et al, 21 found significant variability in gross motor development and body tone.…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…Greater numbers of studies are confirming the correlation between positional plagiocephaly and neurodevelopmental delay seen in fine motor skills. 7,9,12,19 Whether the developmental delay or the plagiocephaly is the causative factor remains unanswered. The importance of regular repositioning and observed tummy time cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…Deformational plagiocephaly was associated with a decrement in Bayley Scales of Infant Development scores (p < 0.001), most significantly evident in motor functions. 27 It is likely, however, that any difference in motor development between these 2 groups is simply due to spending less time in the prone position, and not due to the positional plagiocephaly. In addition to motor development, a 1259-patient retrospective study showed a trend correlating deformational plagiocephaly with otitis media, possibly because of plagiocephalic developmental alteration of the eustachian tube.…”
Section: Sequelaementioning
confidence: 97%